Análise molecular de gymnotus (Pisces, gymnotiformes) do rio Piquiri, na bacia do alto rio Paraná, e do rio Turvo Sujo - Siriani, Selma Torres (2009)
The Gymnotus genre has wide distribution in the Neo-tropical region. After more than two centuries of taxonomic stability, Gymnotus carapo (banded knifefish) was re-described in several other species. However, many questions remain about the validity of many species considered valid. In this work, the molecular characterization of Gymnotus paraguensis, Gymnotus sylvius and Gymnotus pantanal species was done, as well as the comparison with some genetic strains of Gymnotus from the basin of the Doce River. We evaluated the genetic variability by analyzing the ATPase 6/8 region of mtDNA and the evaluation of the nucleotide diversity level found among the groups was expanded. The Nucleotide diversity and the built trees with TRN + I model demonstrated the genetic differentiation among the G. paraguensis, G. sylvius and G. pantanals pecies and the genetic lineage from the basin of the Doce River. The results show that there is a need for further evaluation of the Gymnotus lineage from the basin of the Doce River, both genetic and taxonomic.